Dual Axl/MerTK inhibitor INCB081776 creates a proinflammatory tumor immune microenvironment and enhances anti‐PDL1 efficacy in head and neck cancer. Issue 5 (20th March 2023) - Kostecki, Kourtney L.; Iida, Mari; Wiley, Anne L.; Kimani, Stanley; Mehall, Bridget; Tetreault, Kaitlin; Alexandridis, Roxana; Yu, Menggang; Hong, Seungpyo; Salgia, Ravi; Bruce, Justine Y.; Birge, Raymond B.; et al.
Abstract: Background: The tyrosine kinase receptors Axl and MerTK are highly overexpressed in head and neck cancer (HNC) cells, where they are critical drivers of survival, proliferation, metastasis, and therapeutic resistance. Methods: We investigated the role of Axl and MerTK in creating an immunologically "cold" tumor immune microenvironment (TIME) by targeting both receptors simultaneously with a small molecule inhibitor of Axl and MerTK (INCB081776). Effects of INCB081776 and/or anti‐PDL1 on mouse oral cancer (MOC) cell growth and on the TIME were evaluated. Results: Targeting Axl and MerTK can reduce M2 and induce M1 macrophage polarization. In vivo, INCB081776 treatment alone or with anti‐PDL1 appears to slow MOC tumor growth, increase proinflammatory immune infiltration, and decrease anti‐inflammatory immune infiltration. Conclusions: This data indicates that simultaneous targeting of Axl and MerTK with INCB081776, either alone or in combination with anti‐PDL1, slows tumor growth and creates a proinflammatory TIME in mouse models of HNC.